Problems and Obligations in the Division of Children's Inheritance According to Islamic Law - Kamumu, Yulin (Damhil Law Journal, 2022)
Islamic law establishes the rules of inheritance in a very organized and just manner. When the right of ownership of property is established for every human being, both men and women in a legal way. The purpose of this article is to find out the problems and obligations in the division of children's inheritance according to Islamic law.Â  In writing this research, the method that the author uses is normative juridical research method with data sources using secondary data. the result of this study is that there are still many people who do not know about Islamic inheritance law, so it is necessary to reflect fair inheritance law, namely by paying attention to the conditions that must be met before the distribution of inheritance in order to achieve happiness and justice. Because the principle of Islamic law is for the benefit of the people or rahmatan lil alamin, which is a mercy to reach consensus and not ally in things that are not pleased by Allah.